2016
DOI: 10.1039/c6py00661b
|View full text |Cite
|
Sign up to set email alerts
|

Transparent superhydrophobic coatings from amphiphilic-fluorinated block copolymers synthesized by aqueous polymerization-induced self-assembly

Abstract: Preparation of transparent and superhydrophobic coatings by co-deposition of an aqueous solution of an amphiphilic fluorinated block copolymer with silica was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…Due to the inherent nano-/microstructure throughout the whole bulk material the superhydrophobic properties are insensitive to abrasion. This is a major advantage over state-of-the-art superhydrophobic coatings such as deposited nanoparticles, [66][67][68] etched, [69,70] anodized, [71] or imprinted surfaces [72] or surfaces made by phase-separation effects [73,74] which are often fragile single layers and very sensitive to abrasion. Since the pore size of Fluoropor foam is smaller than the wavelength of visible light the material is optically transparent (see Figure 4a) making these materials applicable for real-world applications like window coatings, etc.…”
Section: Fluorinated Polymers With Enhanced Performancementioning
confidence: 99%
“…Due to the inherent nano-/microstructure throughout the whole bulk material the superhydrophobic properties are insensitive to abrasion. This is a major advantage over state-of-the-art superhydrophobic coatings such as deposited nanoparticles, [66][67][68] etched, [69,70] anodized, [71] or imprinted surfaces [72] or surfaces made by phase-separation effects [73,74] which are often fragile single layers and very sensitive to abrasion. Since the pore size of Fluoropor foam is smaller than the wavelength of visible light the material is optically transparent (see Figure 4a) making these materials applicable for real-world applications like window coatings, etc.…”
Section: Fluorinated Polymers With Enhanced Performancementioning
confidence: 99%
“…Ouhib et al have recently reported an approach to develop SHS using SNP and fluorinated amphiphilic BCP prepared via an RAFT-mediated PISA process. 38 However in that case, the mixture of SNP and BCP was able to show superhydrophobicity only after annealing at 150 8C.…”
mentioning
confidence: 90%
“…The polymerization of fluorinated monomer by such a process was recently reported by Zhou et al However, the formation of fluoropolymer particles was very much dependent on the pH of the medium. Ouhib et al have recently reported an approach to develop SHS using SNP and fluorinated amphiphilic BCP prepared via an RAFT‐mediated PISA process . However in that case, the mixture of SNP and BCP was able to show superhydrophobicity only after annealing at ∼150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of approaches for both applying roughness and structuring the surface as well as for covering the surface with different compounds with low surface energy have been proposed. Up to now, a variety of rough surfaces have been prepared using chemical etching, 6 lithography, 7 laser microstructuring, 8 applying nanoparticles, [9][10][11][12] or nanofibers 13 of different nature, mechanical treatment such as pressing rough templates to the substrate 14 and many other methods, such as depositing candle soot on a substrate. 15 Substances containing nonpolar groups such as CH 2 , CH 3 , CF 2 , CF 3 , can be used before or after roughening to achieve low surface energy.…”
Section: Introductionmentioning
confidence: 99%